Karakteristik Ekstrak Kulit Tanduk Kopi Sebagai Sumber Antioksidan Pada Variasi Ukuran Partikel Dan Lama Ekstraksi Dengan Metode Microwave Assisted Extraction - Sudiantari, Gusti Ayu Sri; Putra, Gusti Putu Ganda; Anggreni, Anak Agung Made Dewi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2026)
Coffee husk is a by-product of the hulling process of coffee beans, containing bioactive compounds such as phenols and flavonoids that have potential as natural antioxidants. This research aimed to determine the effect of particle size and extraction time using the Microwave Assisted Extraction (MAE) method on the characteristics of coffee husk extract and to identify the best combination of traetments to produce coffee husk extract as an antioxidants source. The research was conducted using a factorial Randomized Block Design (RBD) with two factors: particle size (40,60,80 mesh) and extraction time (6, 8, 10, 12, 14 minutes). The data obtained were analyzed using analysis of variance (ANOVA), followed by the Honest Significant Difference (HSD) test. The observed parameters included extract yield, total phenol, total flavonoid, and antioxidants capacity. The result showed that both particle size and extraction time had a significant effect on all tested parameters. The best treatment was found with a particle size of 80 mesh and an extraction time of 14 minutes, resulting in an extract yield of 6.56 ± 0.44%, total phenol content of 4.64 ± 0.00 mg GAE/g, total flavonoid content of 9.58 ± 0.11 mg QE/g, and antioxidant capacity of 0.96 ± 0.01 mg GAEAC/g.